Pengaruh Good Corporate Governance, Firm Size, dan Independensi Auditor terhadap Integritas Laporan Keuangan - Deski Arivan; Hermie Hermie (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Management of a business must always be carried out with the aim of advancing the interests of the company, and this is what is meant by "good corporate governance". There are three sizes of business: large conglomerates, large corporations, and small businesses. Large companies are often more profitable than small companies due to the high operating costs associated with managing revenue and large asset bases. This research uses quantitative methods with a sample of 72 mining companies listed on the Indonesia Stock Exchange (BEI) which then carries out multiple regression analysis. The results conclude that Institutional Ownership has an effect on the Integrity of Financial Reports, the Proportion of Independent Commissioners has an effect on the Integrity of Financial Reports, Firm Size has an effect on the Integrity of Financial Reports, and Auditor Independence has a positive and significant effect on the Integrity of Financial Reports.